Innovation in Education through Student Final Project - Muslimah Susilayati (International Islamic Schools Alliance, 2016)
To optimize the role and education function, university needs realistic experiment, continuously develops itself to meet the challenge and society and industrial demand. That efforts can be done by preparing students for making innovation in education through research & development of the final project. This study is aim to provide an overview about the steps taken to provide student to create innovation in education. This is a library reasearch. The data was taken from written materials through literary studies. The result of study are showed that innovation in education can be done through student final project by using R&D experiment, action reasearh, and qualitatif reasearch. There are four steps in R&D experiment, those are 1) developing model; 2) validating model; 3) trial; and 4) analyzing the result of the trial and polishing model. Furthermore, in action research and qualitative reseach, objective of model formulation and development process are required. The product of innovation in education can be in form of a model, a method, a procedure, a book, a module, an evaluating instrument, and a learning program, that have been passed quality test so eligible to be used in education.